ANALYSIS OF THE FEASIBLITY STUDY OF THE AMBON BANANA WHOLESALE BUSINESS UD. BAIM PUTRA IN HUMAN RESOURCES, MARKET AND MAKERTING ASPECTS - Alfiani, Farisha; Salsabila, Zahra; Anggraeni, Rosiana; Jiani, Anggi; Ken, R.R Wening (Universitas Muhammadiyah Tangerang, 2024)
Ambon Banana Business UD. Baim Putra has high quality and many health benefits. A business feasibility study is a comprehensive assessment of an important part of the business. The purpose of a business feasibility study is to determine whether or not the business to be run is feasible. Research on the Ambon banana wholesale business. UD. Baim Putra uses qualitative methods. The bananas sold come from PT. Mulya Raya and then sold to Cibitung Main Market. Each Ambon banana has a banana type code to distinguish its quality. The results showed that Ambon banana UD. Baim Putra has a fairly good sales level at the Cibitung Main Market. Baim Putra bananas are considered healthy and high quality Ambon bananas. Apart from that, high quality Ambon bananas can be sold because of the large and strategic land they own.